Coming and going to a surgical center, the evaluation of risks in transport of patients in a university hospital in Brazil (Bioscience Journal, 2020)
The patient’s in-hospital transport is an activity that must be performed with safety and quality and involves considerable risks, especially for surgical patients. The objective of this study was to evaluate the adequacy or not of transport of surgical patients from inpatient units to surgical centers and vice-versa. The transport and patient profile, the nursing workload, the professionals and conditions involved were assessed for each patient (or transport), and subsequently the transports were evaluated as inadequate (some non-conformity) or adequate. The transport was inadequate in 39.3% of the evaluations. The most common non-conformities were the lack of knowledge of the transport at the patient’s destination, incorrect documents, patient alone during the route, and absence of health professional during transport (when necessary). In this institution and in the period evaluated, the transport was mainly run by porter. Patients in rout to inpatient units have higher frequency of inadequate transport, mainly because of lack of communication with the destination unit. The increase in workload, evaluated by the Santos Score, also increased the risk of having inappropriate transport (OR = 1.21, CI95%: 1.08-1.16), and when the patients were grouped in minimal care versus non-minimal care, the latter also showed higher risk of inadequate transport. When the transports were evaluated separately by route, patients going to surgical centers had a higher risk when the Santos Score increased (OR = 1.168, CI95%: 1.07-1.27), and patients going to inpatient units had a lower risk when the Santos Score increased (OR = 0.605, CI95%: 0.46-0.80). In the last case, patients with a high workload were also accompanied by health professionals. The presence of a health professional when the patient was going to an inpatient unit also decreased the risk of inadequate transport (OR = 0.011, CI95%: 0.002-0.070). The patient returning to their origin unit showed more transport non-conformities. Perhaps the reason is the discredit attributed to risk in these patients once the surgical problem was solved. Thus, it is a fact that the patient nursing workload and the route of the transport were effective in predicting the risk of inadequate transport, being of great potential for practical use.